Gonadotrophin-mediated miRNA expression in testis at onset of puberty in rhesus monkey: predictions on regulation of thyroid hormone activity and DLK1-DIO3 locus. (25th January 2019) - Aliberti, Paula; Sethi, Rahil; Belgorosky, Alicia; Chandran, Uma R; Plant, Tony M; Walker, William H
Abstract: Molecular mechanisms responsible for the initiation of primate spermatogenesis remain poorly characterized. Previously, 48 h stimulation of the testes of three juvenile rhesus monkeys with pulsatile LH and FSH resulted in down-regulation of a cohort of genes recognized to favor spermatogonia stem cell renewal. This change in genetic landscape occurred in concert with amplification of Sertoli cell proliferation and the commitment of undifferentiated spermatogonia to differentiate. In this report, the non-protein coding small RNA transcriptomes of the same testes were characterized using RNA sequencing: 537 mature micro-RNAs (miRNAs), 322 small nucleolar RNAs (snoRNAs) and 49 small nuclear RNAs (snRNAs) were identified. Pathway analysis of the 20 most highly expressed miRNAs suggested that these transcripts contribute to limiting the proliferation of the primate Sertoli cell during juvenile development. Gonadotrophin treatment resulted in differential expression of 35 miRNAs, 12 snoRNAs and four snRNA transcripts. Ten differentially expressed miRNAs were derived from the imprinted delta-like homolog 1-iodothyronine deiodinase 3 ( DLK1 - DIO3 ) locus that is linked to stem cell fate decisions. Four gonadotrophin-regulated expressed miRNAs were predicted to trigger a local increase in thyroid hormone activity within the juvenile testis. The latter finding leads us to predict that, in primates, a gonadotrophin-induced selective increase in testicular thyroid hormone activity, together with the established increase in androgen levels, at the onset of puberty is necessary for the normal timing of Sertoli cell maturation, and therefore initiation of spermatogenesis. Further examination of this hypothesis requires that peripubertal changes in thyroid hormone activity of the testis of a representative higher primate be determined empirically.